Pillars of Faith : American Congregation and Their Partners. - Ammerman, Nancy Tatom, 1950- (University of California Press, 2001)
At the close of the twentieth century the United States was, by all accounts, among the most religious of modern Western nations. Pillars of Faith describes the diversity of tradition and the commonality of organizational strategy that characterize the more than 300,000 congregations in the United States, arguing that they provide the social bonds, spiritual traditions, and community connections that are vital to an increasingly diverse society.